KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 13 PADANG - Sari, Intan Permata; Ratna, Ellya; Hafrison, Mhd. (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is to describe reading skills, writing skills and describe the contribution of reading skills to the description of text description skills in writing description texts of class VII students of SMP Negeri 13 Padang. This type of research is quantitative with descriptive method. The population of this study was Grade VII students of SMP Negeri 13 Padang, which were 224 students. The sample in this study was determined by proportional random sampling of 15% of the population, namely 35 students. The results of the study on reading skills in understanding the description text of students are in good qualification (B) with an average of 82.71. In writing description text skills students are in good qualification (B) with an average of 83.10. On the contribution of reading skills, the understanding of the description text towards the students' writing text writing skills is 94.48%. The better the reading skill of understanding the description text, the better the writing skills of the text description. Thus, to be skilled in writing the description text of class VII students of SMP Negeri 13 Padang, good reading comprehension skills are also needed.Â Kata Kunci: Kontribusi, keterampilan membaca pemahaman teks deskripsi, Â keterampilan menulis teks deskripsi